Diagnosis of appendicitis: comparison of computed tomography (CT) scans using oral contrast material alone versus oral and intravenous (IV) contrast media - Sutiratchaichan, Porntip; Kamphan, Sirinapa (Biomedical Sciences and Clinical Medicine, 2024)
Objectives The purpose of this study was to compare the diagnostic accuracy between computed tomography (CT) scans using oral contrast material alone (oral contrast CT) versus oral and intravenous (IV) contrast media (contrast-enhanced CT) in patients with equivocal symptoms and signs of appendicitis. Methods This retrospective study had 103 patients, who were aged from 15 to 94 years, with equivocal symptoms and signs of appendicitis. All of the patients were given oral contrast material, and a CT scan was performed one hour later. Immediately thereafter, a repeated CT scan of the abdomen was performed following intravenous administration of contrast-enhanced media. Studies were separated and interpreted independently by two radiologists, who were blinded to medical records. The fi nal outcome was based on operative and clinical findings, and follow-up data. Results Of the 103 patients enrolled, seven underwent only oral contrast CT because they had contraindication for IV contrast media. Data analysis of the contrast-enhanced CT and oral contrast CT revealed sensitivity of 89.4% and 83.3% (p=0.55), specifi city of 95.9% and 96.4% (p=1.00), PPV of 95.5% and 95.2% (p=1.00), NPV of 90.4% and 86.9% (p=0.77), and accuracy of 92.7% and 90.3% (p=0.62), respectively. An alternative diagnosis was established in 30 of the patients (29.1%), which included 12 with gastrointestinal abnormality, 10 with urinary tract abnormality, six with gynecologic abnormality, and two with other abnormalities. Conclusions Patients presenting with suspected acute appendicitis had similar characteristics to those diagnosed as appendicitis when CT scans used either oral contrast material alone or oral and IV contrast media.